2021
DOI: 10.3390/polym13193361
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biopolymer Chitosan on the Rheology and Stability of Na-Bentonite Drilling Mud

Abstract: The utilization of greens resources is a grand challenge for this century. A lot of efforts are paid to substitute toxic ingredients of the conventional drilling mud system with nontoxic natural materials. In this paper, the effect of the natural polymer chitosan on the rheology and stability of sodium-bentonite drilling mud was investigated in the polymer concentration range of 0.1–3.0 wt.%. Both the shear and time dependent rheological properties of pure chitosan, pure bentonite and bentonite–chitosan disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Indeed, the solution less diluted (0.5% of Ch) behaves as Newtonian fluids, meaning that interactions with biopolymer–water prevailed [ 28 ]. Similarly, Abu-Jdayil et al [ 14 ], working on the effect of Ch (0.1–3%), observed a non-Newtonian behavior overall, except for Ch ≤ 0.5%.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Indeed, the solution less diluted (0.5% of Ch) behaves as Newtonian fluids, meaning that interactions with biopolymer–water prevailed [ 28 ]. Similarly, Abu-Jdayil et al [ 14 ], working on the effect of Ch (0.1–3%), observed a non-Newtonian behavior overall, except for Ch ≤ 0.5%.…”
Section: Resultsmentioning
confidence: 78%
“…Benoso et al [ 12 ] prepared Ch solutions with different pH using Ac solutions and verified that their ξ-potential, which measures the net charge of the macromolecule in the solution, was always positive, decreasing linearly from 70 to 38 mV when the pH increased from 3.5 to 6.0 and confirming that the protonation was dependent on pH. Abu-Jdayil et al [ 14 ] observed that the ξ-potential for the Ch solution slightly decreased to almost zero mV by increasing the Ch, as a consequence of the Ch effect on the final pH of solutions prepared with constant Ac.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations